137k views
2 votes
Fill in the blanks to complete the description of how to solve the equation.

28x − 56 = 22x − 65.

First, get the variable on the left–hand side of the equation by subtracting 22x from both sides to get
x − 56 = −65. Next, use the
 property of equality to isolate the variable.

2 Answers

2 votes

Answer:

First answer is 6 and the next answer is Addition Property of Equality

Explanation:

User Suntrop
by
4.5k points
0 votes

Answer:

The value of x is the given expression is
(-3)/(2)

Explanation:

Given equation is 28x-56=22x-65

To simplify the given equation as below:

28x-56=22x-65

Subtracting 22x on both sides we get

28x-56-22x=22x-65-22x

6x-56=-65 ( adding the like terms )

Adding 56 on both sides we have

6x-56_56=-65+56

6x=-9

Dividing by 9 on both sides


(2x)/(3)=-1

Multiply into
(3)/(2) on both side


(2x)/(3)*((3)/(2))=-1*((3)/(2))


x=(-3)/(2)

Therefore
x=(-3)/(2)

The value of x is the given expression is
(-3)/(2)

User Erbdex
by
5.4k points